Maternal veterinary occupation and adverse birth outcomes in Washington State, 1992–2014: a population-based retrospective cohort study. Issue 5 (24th February 2018) - Meisner, Julianne; Vora, Manali V; Fuller, Mackenzie S; Phipps, Amanda I; Rabinowitz, Peter M
Abstract : Objective: Women in veterinary occupations are routinely exposed to potential reproductive hazards, yet research into their birth outcomes is limited. We conducted a population-based retrospective cohort study of the association between maternal veterinary occupation and adverse birth outcomes. Methods: Using Washington State birth certificate, fetal death certificate and hospital discharge data from 1992 to 2014, we compared birth outcomes of mothers in veterinary professions (n=2662) with those in mothers in dental professions (n=10 653) and other employed mothers (n=8082). Relative risks (RRs) and 95% CIs were estimated using log binomial regression. Outcomes studied were premature birth (<37 weeks), small for gestational age (SGA), malformations and fetal death (death at ≥20 weeks gestation). Subgroup analyses evaluated risk of these outcomes among veterinarians and veterinary support staff separately. Results: While no statistically significant associations were found, we noted a trend for SGA births in all veterinary mothers compared with dental mothers (RR=1.16, 95% CI 0.99 to 1.36) and in veterinarians compared with other employed mothers (RR=1.37, 95% CI 0.96 to 1.96). Positive but non-significant association was found for malformations among children of veterinary support staff. Conclusions: These results support the need for further study of the association between veterinary occupation and adverse birth outcomes.